Improving the Achievement of the Fifth Grade Students of SDN 1 Sebatu in English Vocabulary by Using Puppets as Teaching Media - ., Pande Made Ari Saguna; ., Dr.Sudirman, M.L.S; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk meningkatkan prestasi kosa kata bahasa inggris murid kelas 5 SDN 1 Sebatu dengan menggunakan wayang sebagai media.Subjek dari penelitian ini adalah kelas 5 SDN 1Sebatu dengan jumlah 41 murid. Penelitian ini menggunakan prosedur Classroom Action Research (PTK) dan Diselesaikan dalam dua siklus. Hasil dari penelitian ini menunjukan bahwa pembelajaran menggunakan wayang sebagai media dapat meningkatkan prestasi kosa kata murid kelas 5 SDN 1 Sebatu. Hasil post-test II menunjukan bahwa nilai rata-rata yang diperoleh dari murid kelas 5 berjumlah 82.31.Sedangkan hasil test awal (pre-test) nilai rata-rata yang diperoleh berjumah 51.00. Persentase jumlah murid yang lulus tes juga meningkat dari 39.03% menjadi 58.54%. Hasil dari pecentase kelulusan yang diperoleh dari post-test II dengan jumlah 97.56% sudah melebihi dari target yang ditetapkan dengan jumlah 85.00%. Hasil kuesioner juga menunjukan bahwa murid memberikan kesan yang positif terhadap pembelajaran bahasa inggris dengan menggunkan wayang sebagai media. Pembelajaran bahasa inggris menggunakan wayang sebagai media dapat meningkatkan motivasi dan konsentrasi belajar.Kata Kunci : wayang, prestasi kosa kata This study aimed at improving the achievement of the fifth grade students of SDN 1 Sebatu in English vocabulary by using puppets as teaching media. The subjects of this study were the fifth grade students of SDN 1 Sebatu which consisted of 41 students. The study was conducted by following the action research procedures and it was completed in two cycles. The result of the study showed that achievement of the fifth grade students in English vocabulary could be improved by using puppets. The result of post-test II showed that the studentsâ mean score was 82.31 which significantly improved from the pre-test result that was 51.00. The class percentage of the students passing the test also improved from 39.02% to 58.54%. The total class percentage of the students passing the test was 97.56 % which was beyond the expected target which was 85.00%. Based on the questionnaire result, the students also had positive response towards the implementation of the puppets. The result showed that learning English using puppets could improve their motivation, interest, attention, and concentration.keyword : puppets, vocabulary achievement